Climate change impacts on Egyptian aquaculture: challenges, opportunities, and research gaps - Dalia M. M. Yacout; Hanady H. Khalil; Mohamed M. Yacout (Frontiers in Sustainable Food Systems)
The Egyptian aquaculture sector is subjected to several threats caused by climate change, including a considerable decline in Nile River flow, the sea level rise with the risk of inundation, salty-water intrusion, and the loss of productive farms besides increases in temperatures and decreased water supplies. Due to other urgent issues in Egypt, such as rising food and living expenses and decreased land productivity along the coast, climate change has recently risen to the top of the priority list for national decision-makers. This study aims to highlight climate change impacts on Egyptian aquaculture food systems considering the three sustainability pillars: environmental, economic, and social. We also highlighted the related challenges, opportunities, and research gaps to suggest future needs for further studies. National efforts to improve the local aquaculture sector were presented, as well as potential opportunities for climate change adaptation strategies. The results of this study are intended to assist researchers, policy, and decision-makers in developing strategies that would help in mitigating climate change impacts on the aquaculture sector, to assist sustainably expanding aquaculture food systems, and to enhance local food security. The study reveals that the most productive fish farms in the coastal lakes, mainly brackish, are vulnerable to sea level rise with expectations of salty-water intrusion and disturbance of the cultivated species and loss of aquaculture farms with the consequent environmental and socio-economic impacts. Data availability is one of the main challenges that face academics interested in the aquaculture field. Research fields such as hydrodynamics, remote sensing, geographical information systems and life cycle assessment are promising fields that can contribute to the prediction of climate change impacts on aquaculture systems which helps in developing proper mitigation strategies. Socioeconomic aspects that need to be considered include climate change impacts on living conditions and the physical well-being of small-scale aquaculture farmers, the vulnerability of small-scale farms related to their location, circumstances, disadvantages, and labor challenges. Solar energy usage expansion, development of hatcheries for fry production, expansion in integrated fish farming in reclaimed lands, water-return maximizing and usage of intensive and semi-intensive systems are all some of the strategies adapted by national authorities to mitigate the climate change impacts on local aquaculture sector. Furthermore, the involvement of investors, policy and decision makers is a must to expand the Egyptian aquaculture sector in a sustainable way. Regulations must be set to encourage investments in sustainable technologies as aquaponics, desalination and water recycling. Funds can be provided to stimulate the research and development in in this sector. A national awareness campaign among farmers to explain the potential impacts of climate change on local aquaculture farms and how to adapt is highly recommended, and enhancing collaboration and communication between local stakeholders “researchers, investments, policy makers and farmers” is a must.